Relationship Between Interleukin-28B Gene Polymorphism and Chronic Hepatitis B Infection - Alandağ, Celal; Demirel, Ulvi; Kargün, Kürşat (My University, 2022)
Aim: Interleukin 28B (IL28B) gene polymorphism may play a role in hepatitis B virus (HBV) infection prognosis. We investigated the effects of IL28B gene polymorphism on viral clearance and viral load in chronic hepatitis B (CHB) patients.Material and Methods: We included 146 individuals who applied to our center between October 2011 and October 2012. CHB (N=117) and control (N=29) groups were compared in terms of IL28B gene rs12979860, rs12980275 gene region polymorphisms, and IL28B gene expression (mRNA) levels.Results: There was no statistically significant difference between groups in terms of rs12979860 gene region polymorphism rates (?2=0.36, p=0.835). But there was a significant association between groups in terms of rs12980275. In the CHB group, the A/A genotype was much more, (?2=55.2, p<0.001), G/A and G/G genotypes were less frequent. There was no statistically significant difference between the groups in terms of IL28B expression levels.Conclusion: This study revealed the genotype profile of the IL28B gene of our region. It is the first study on this subject in our region. The association between CHB and rs12980275 polymorphism may be important. Our results will contribute to future studies.
Keywords: Turkey; Chronic hepatitis B; IL 28B polymorphism; IL 28B expression